The impact of maternal touch of the abdomen on cardiotocography fetal patterns - Alex S. Rolland Souza; Emanuela V. V. Cavalcante; Candice A. Macedo; Stênio G. Freitas; Amanda T. P. Figueiredo; Susi A. Alves; Thaíse C. A. C. Silva; Gustavo F. deAlbuquerque Souza; João G. Alves (Brain and Behavior, 2019)
Abstract Introduction Some studies suggest that maternal touch of the abdomen produces an increase in the number of movements of the fetus. However, the influence of maternal touch of the abdomen on fetal cardiotocography patterns has not been studied. Methods This nonrandomized, before‐after clinical trial that assessed fetal cardiotocography patterns during maternal touch of the abdomen in 28 low‐risk pregnant women. Results Baseline fetal heart rate, accelerations, decelerations, and variability did not change with maternal touch of the abdomen, but fetal movements increased (p = 0.044). Conclusion Fetal movements increases during maternal touch of the abdomen.